2002
DOI: 10.1128/iai.70.7.3944-3947.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Protease Activity and Histamine Release from the Human Mast Cell Line HMC-1 Stimulated by Recombinant Streptococcal Pyrogenic Exotoxin B/Streptococcal Cysteine Protease

Abstract: We constructed the expression vector pSK-SCP containing the streptococcal exotoxin B gene (spe b) which expressed protease activity. We showed that the recombinant streptococcal pyogenic exotoxin B/streptococcal cysteine protease (rSPE B/SCP) was secreted into the culture supernatant of the transformant and retained its SCP activity, which was equivalent to or greater than that of the naturally occurring molecule. The secreted rSPE B/SCP induced histamine release and degranulation of the human mast cell line H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…SpeBm hydrolysis of H-kininogen in vitro and in vivo leads to release of the nona-peptide bradykinin, a potent vasodilator and inducer of pain, which most likely contributes to the pathophysiology of invasive S. pyogenes infections (Herwald et al , 1996 ). Another proinfl ammatory activity described for SpeBm is the induction of histamine release and degranulation of mast cells (Watanabe et al , 2002 ). The mechanism for the activity on mast cells is still unclear, but it seems to be coupled to SpeBm proteinase activity and could be a contributing factor to STSS (Navarre and Schneewind , 1999 ).…”
Section: Spebm Activity On the Human Immune Systemmentioning
confidence: 99%
“…SpeBm hydrolysis of H-kininogen in vitro and in vivo leads to release of the nona-peptide bradykinin, a potent vasodilator and inducer of pain, which most likely contributes to the pathophysiology of invasive S. pyogenes infections (Herwald et al , 1996 ). Another proinfl ammatory activity described for SpeBm is the induction of histamine release and degranulation of mast cells (Watanabe et al , 2002 ). The mechanism for the activity on mast cells is still unclear, but it seems to be coupled to SpeBm proteinase activity and could be a contributing factor to STSS (Navarre and Schneewind , 1999 ).…”
Section: Spebm Activity On the Human Immune Systemmentioning
confidence: 99%
“…SpeB has a variety of mammalian substrates for its proteolytic activity, including interleukin-1␤ precursor, vitronectin, fibronectin, laminin, urokinase plasminogen receptor, and kininogens (14,18,20,36). In addition, this molecule induces mast cell degranulation (35) and activates the 66-kDa human endothelial cell matrix metalloprotease and has therefore been associated with endothelial cell damage (5). The potential degradation of a large variety of streptococcal exoproteins and M protein by SpeB may also influence virulence (19,22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SpeB directly cleaves and inactivates the antibacterial peptide LL-37, which is capable of killing S. pyogenes (96). Moreover, a recent study showed that purified SpeB stimulates the release of histamine from a human mast cell line (113). Some reports have suggested that SpeB also functions as a superantigen, with stimulation of T lymphocytes without antigen presentation, and that the activity is independent of the proteolytic activity (30,64).…”
Section: Microbial Immunoglobulin Proteasesmentioning
confidence: 99%